Pengaruh Aset Pajak Tangguhan, Financial Distress, dan Ukuran Perusahaan Terhadap Manajemen Laba - Chris Meytaliana, Adellia; Indra Pahala; Hafifah Nasution (Jurnal Ilmiah Cano Ekonomos, 2024)
This research aims to analyze the impact of deferred tax assets, financial distress, and company size on earnings management. This research is quantitative research with secondary data types. The population of this research is all healthcare sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The research sample was selected using purposive sampling, with a final number of observations of 59. Data was obtained from the company's Annual Financial Report, which was then processed using Eviews 12. Panel Data Regression Analysis was carried out to analyze the processed data. The results of this research show that deferred tax assets have a positive and significant effect on earnings management. In contrast, financial distress and company size do not have a significant effect on earnings management. This research requires companies to increase their internal supervision regarding the use of deferred tax assets to ensure that there is no manipulation of these assets, which could be detrimental to the company in the future. Transparency in reporting and complying with applicable accounting standards is the key to preventing earnings management actions and increasing stakeholder trust.